2011
DOI: 10.1111/j.1651-2227.2011.02439.x
|View full text |Cite
|
Sign up to set email alerts
|

Overweight does not increase asthma risk but may decrease allergy risk at school age after infantile bronchiolitis

Abstract: Previous or current overweight does not increase asthma or allergy risk but current obesity may decrease allergy risk at school age after bronchiolitis in infancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Results from cohort studies on the association between AD and BMI in older children are conflicting, with some studies reporting a positive association [19, 20], some studies reporting no association [25] and one study reporting a negative association [26]. A meta-analysis of studies in children, adolescents and adults concluded that overweight/obesity is associated with an increased prevalence of AD in North American and Asian countries, but not in European countries [2].…”
Section: Discussionmentioning
confidence: 99%
“…Results from cohort studies on the association between AD and BMI in older children are conflicting, with some studies reporting a positive association [19, 20], some studies reporting no association [25] and one study reporting a negative association [26]. A meta-analysis of studies in children, adolescents and adults concluded that overweight/obesity is associated with an increased prevalence of AD in North American and Asian countries, but not in European countries [2].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that among the forty-five articles reviewed in this study there are also two articles that concluded that no correlation between asthma and Body Mass Index could be found [22,23]. Another articled also mentioned that no relation between weight change in either direction and the incidence or persistence of asthma could be found [24].…”
Section: Obesity Indicators Relation With Asthmamentioning
confidence: 98%
“…After review of the titles and abstracts, 536 articles did not meet our inclusion criteria, and 12 were excluded 31-42 for a lack of data for the frequency of AD/eczema or BMI classification. In total, 30 studies 26,33, were included in the review, of which 20 had valid data that could be pooled to assess for the effects of overweight, 26,43,47,50,[53][54][55][56][57][59][60][61][62][63][64][65][66][67][68][69] 23 for obesity, 26,33,43,45,47,50,[52][53][54][55][56][57][59][60][61][62][63][64][65][66][67][68][69] and 26 for overweight/obesity. 26,43,44,[46]…”
Section: Literature Searchmentioning
confidence: 99%